A Comprehensive Practice Guideline for Magnetic Resonance Imaging Compatibility in Implanted Neuromodulation Devices. Issue 7 (18th August 2020) - Sayed, Dawood; Chakravarthy, Krishnan; Amirdelfan, Kasra; Kalia, Hemant; Meacham, Kathleen; Shirvalkar, Prasad; Falowski, Steven; Petersen, Erika; Hagedorn, Jonathan M.; Pope, Jason; Leever, John; ,; et al.
Abstract: Objectives: The evolution of neuromodulation devices in order to enter magnetic resonance imaging (MRI) scanners has been one of understanding limitations, engineering modifications, and the development of a consensus within the community in which the FDA could safely administer labeling for the devices. In the initial decades of neuromodulation, it has been contraindicated for MRI use with implanted devices. In this review, we take a comprehensive approach to address all the major products currently on the market in order to provide physicians with the ability to determine when an MRI can be performed for each type of device implant. Materials and Methods: We have prepared a narrative review of MRI guidelines for currently marketed implanted neuromodulation devices including spinal cord stimulators, intrathecal drug delivery systems, peripheral nerve stimulators, deep brain stimulators, vagal nerve stimulators, and sacral nerve stimulators. Data sources included relevant literature identified through searches of PubMed, MEDLINE/OVID, SCOPUS, and manual searches of the bibliographies of known primary and review articles, as well as manufacturer‐provided information. Results: Guidelines and recommendations for each device and their respective guidelines for use in and around MR environments are presented. Conclusions: This is the first comprehensive guideline with regards to various devices in the market and MRI compatibility from the American Society of Pain and Neuroscience.